Konversi Energi Magnetik Ke Energi Mekanik Pada Alat Peraga Menggunakan Kawat Besi - Ramadhina Dinda Safitri; Fitri Rayhani; Herma Widya (Journal on Education, 2024)
This research discusses making teaching aids using simple materials such as iron wire, batteries and magnets. By using the help of magnetic attraction which will produce motion energy. This prop utilizes the attractive properties of magnets. With components such as iron wire, magnets and batteries, the iron wire will be attracted by the existing magnetic field and will produce movement energy in the iron wire. The aim of this research is to find out whether magnetic energy can be converted into mechanical energy in the context of teaching aids. Making teaching aids using simple materials to support students' learning activities regarding Lorenz style learning. The development of sustainable and environmentally friendly alternative energy technology is greatly influenced by this phenomenon. The experimental method used involves the basic principles of electromagnetism to create rotational motion in iron wire. To produce rotational motion in an iron wire, the basics of electromagnetism are applied in experiments. A number of important variables were changed during the experiment, including the type of magnetic material used, the strength of the magnetic field, and the type of iron wire used.